Aphids of the state of Espírito Santo, Brazil (Homoptera: Aphidoidea) - Oliveira, Alda Maria de (2014)
In this paper 16 aphid species (homoptera: Aphidoidea) that seem to represent new records to the state of Espírito Santo in Brazil were listed. They are: Aphis craccivora (Koch), Aphis fabae solanella Theobald, Aphis gossypii (Glover). Aphis nerii (Boyer de Fonscolombe), Aphis spiraecola Patch), Brevicoryne brassicae (L.), Capitophorus hippophaes (Walker), Geopemphigus  floccosus (Moreira), Lipaphis erysimi (Kaltenbach), Myzus (Nectarosiphon) persicae (Sulzer), Picturaphis brasiliensis (Moreira), Rhopalosiphum maidis (Fitch), Rhopalosíphum rufiabdominalis (Sasaki), Toxoptera aurantii (Boyer de Fonscolombe), Toxoptera citricidus (Kirkaldi) and Uroleucon sonchi (Geoffroy). All the aphid specimens were identified by the first author at the British Museum (National History) in London under Dr. V.F. Eastop's supervision. Slides of all aphid species have been kept in the collection of the Department of Entomology and Parasitology at Km 47, Rio de Janeiro, Brazil, and at the British Museum (Natural History) in London.